Educational Innovation in Economics and Business II
XVIII, 395 p.
Keywords: This volume consists of the revised versions I of a selection of papers of the second EDINEB conference, held in Uppsala from 17-19 August 1995. As with the fIrst edition, the conference and these proceedings are rooted in the participant's involvement with 'EDucational INnovation in Economics and Business'. The thematic focus is quality audit, quality assessment and quality improvement, all of them collected in the theme 'In Search of Quality'. For the fIrst EDINEB conference, which took place in Maastricht, December 1993, 'Problem-Based Learning' was chosen as leading theme. The introduction of problem-based learning in the curriculum of any faculty is to be regarded as a major innovation in the educational system. In contrast, the dedication to the search of quality in education resulted in a large variety of case studies and theoretical contributions on educational innovations aiming at increasing the quality of teaching and learning. This contrast between the one major step and the many small steps has been the decisive factor for the editors to compose these proceedings as a kind of allegory of Robert M. Pirsig's famous novel 'Zen and the art of Motorcycle Maintenance, an Inquiry into Values' (ZAMM). Of course, on top of the very obvious reason that the conference had been saddled with a theme that is identical to the title that many critics (probably those who aren't so fond of motorcycling) used to rename ZAMM.